The Realization of Interpersonal Meanings in the Discourse of Abdul Qodir Jaelani - Ahmad Yusri (Universitas Hamzanwadi, 2017)
The present study deals with the realization of interpersonal meanings in the discourse of Abdul Qodir Jailani (AQJ). The aims of this study were to explain the mood, modality, and appraisal systems which are realized in the discourse of AQJ. It used a descriptive qualitative research in the form of discourse analysis. The results uncover that each domain of those three linguistic evidences had its proportion. First, the realization of Mood systems for the four texts was demanding goods and services especially the spoken texts and giving information. Second, the use of modality system was a high proportion that was found in text 1. However, a slight proportion was found in text 2, text 3, and text 4. Third, the realization of appraisal system showed the speakers and the writers feeling on the event including their appreciation, affect, judgment, and amplification. Deeply, it is suggested to conduct further study to create intelligible language in teaching, to make a critical thinker of students, and to produce the best understanding of social practices of the way people do.